2021
DOI: 10.1653/024.103.00409
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Bemisia tabaci (Hemiptera: Aleyrodidae) Mediterranean (Q Biotype) in Landrace and Wild Tomato Populations from Mexico

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Additionally, these results indicate that wild and landrace pepper populations differ in their level of A. eugenii resistance, and are more resistant than cultivated varieties of pepper under nochoice resistance tests. These results support previous studies indicating that cultivated species are less resistant to herbivores than wild and landrace populations (Garzón-Tiznado et al 2020;Millán-Chaidez et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, these results indicate that wild and landrace pepper populations differ in their level of A. eugenii resistance, and are more resistant than cultivated varieties of pepper under nochoice resistance tests. These results support previous studies indicating that cultivated species are less resistant to herbivores than wild and landrace populations (Garzón-Tiznado et al 2020;Millán-Chaidez et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, more eggs were found laid on green leaves than on red leaves of poinsettia, and leaf trichomes occurred at a far greater density on green leaves, nearly 10-fold that of red leaves. Previous studies found similar results, in that a high density of trichomes is favorable for whitefly reproduction in landrace, tomato, and cotton host plants (Acharya and Bhargava 2008, Firdaus et al 2012, Millan-Chaidez et al 2020, Pal et al 2021, Siddiqui et al 2021). That more eggs are laid where there are more trichomes could be due to the latter providing a favorable and safe microclimate for oviposition (Millan-Chaidez et al 2020).…”
Section: Discussionsupporting
confidence: 70%
“…Host plant antibiosis directly affects insect growth, development, and reproduction, serving as a crucial metric for evaluating plant resistance [35]. The variations in the developmental process of B. tabaci among H. mutabilis varieties observed in this study have been documented in crops such as tomato [23], cucumber [25], pepper, and cassava [36,37]. However, information is limited regarding the developmental processes of B. tabaci on different H. mutabilis species.…”
Section: Identification and Evaluation Of Different H Mutabilis Varie...mentioning
confidence: 82%
“…Van et al [ 31 ] proposed an evaluation method based on B. tabaci egg production and adult and nymph survival rates, but this method is labor-intensive and unsuitable for large-scale applications. Taylor [ 22 ] introduced the reproduction index method, validated by Kayani et al [ 32 ] for evaluating cucumber resistance to the southern root-knot nematode, and Millan et al [ 23 ] applied it to analyze and grade tomato resistance to B. tabaci . Using these studies as a basis, we adopted the reproduction index method to assess the resistance level of H. mutabilis to B. tabaci .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation